Consumer Protection in Muamalah Transactions - Risfiana Mayangsari (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
Consumer protection in muamalat transactions is a crucial aspect that underscores the principles of justice and balance in Islamic law. This article examines the mechanisms of consumer protection in muamalat transactions, focusing on consumer rights and the responsibilities of producers or sellers. The research employs a qualitative approach using literature review methods, referencing Islamic legal sources such as the Quran, Hadith, and scholarly fatwas. The findings indicate that fiqh muamalat contains several provisions that explicitly safeguard consumers, such as prohibitions against gharar (uncertainty), riba (interest), and tadlis (fraud). Furthermore, the principles of honesty (sidq) and transparency in transactions are strongly emphasized to ensure that consumers receive clear and comprehensive information about the products or services they purchase. The implications of this study suggest the need for increased awareness and enforcement of laws in muamalat transactions to protect consumers from detrimental practices. The article also recommends strengthening regulations and providing education to business practitioners to ensure compliance with Sharia principles in their operations.